Emotional Intelligence in Times of Covid-19: a Comparative Study in Peruvian Universities - Calle-Ramírez, Xiomara M. (2023)
Objective:The aim of the study was to compare emotional intelligence in Peruvian university students from public and private universities.Theoretical framework: In higher education, emotionally intelligent students have the ability to interact appropriately with others, achieve good academic results, and reach personal and professional goals.Method: The methodology was descriptive-comparative, the sample consisted of 838 university students of both sexes from public (471) and private (364) universities belonging to the coast, highlands and jungle regions of Peru. A sociodemographic form created for the study and the emotional intelligence scale (TMMS-24) were used as measurement instruments.Results and conclusion:The results showed that university students over 30 years of age, women, those from the highlands and those who worked had high levels of emotional intelligence.Implications of the research:It is necessary for university institutions to reorganize their academic conditions and provide the necessary inputs to apply socioemotional strategies to students. Researchers linked to the lines of research on emotional intelligence should develop predictive studies to know which factors may be predicting adequate or inadequate emotional intelligence in university students.Originality:This study demonstrates that it is essential to attend to and provide emotional intelligence tools to those students whodo not have the necessary resources to face different situations in the face of the COVID-19 pandemic and contributes to the training of educators, especially environmental educators in crisis contexts.